The Portuguese National Laboratory of Civil Engineering and the assemble of an architectural research agenda for the promotion of 1960’s-70’s Lisbon new residential neighbourhoods - d'Almeida, P. B.; Marat-Mendes, T. (Proceedings of the 19th International Planning History Society Conference: City Space Transformation, 2022)
World War II imposed massive territorial transformations throughout a number of affected cities, including the provision of housing and new urban infrastructures. To support such societal requests, some governmental research centres, promoted the development of scientific studies to sustain welfare policies. In Portugal, the National Laboratory for Civil Engineering (Laboratório Nacional de Engenharia Civil, LNEC), which responded directly to the Ministry of Public Works, promoted the development of architecture and urban scientific research for such requests. Thus, during the second half of the 20th century, LNEC played a strategic role in guiding the Portuguese urban transformations, including in its capital city, Lisbon. The investigation conducted by LNEC’s architects-researchers, promoted the development of new theoretical research work and the elaboration of architectural and urban plans for specific residential areas. Research and practice were, therefore, articulated and promoted by LNEC. A number of new neighbourhoods planned for Lisbon between 1960’s and 1980’s, benefited from the contribution of LNEC researchers, including Olivais Sul (1959-1968), Chelas (1961-1966) and Restelo (1970-1984). This paper examines, for the above-identified Lisbon’s neighbourhoods, the research contributions, which have guided their architectural and/or urban proposals.